Advancing Corporate Governance in the Banking Sector in Sri Lanka: Assessing Regulatory Frameworks and Supervisory Roles - W. Indira Nanayakkara (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
In the aftermath of the civil war in Sri Lanka, the country has witnessed a significant increase in economic development, with the banking sector assuming a pivotal role in financing growth and fostering economic prosperity. This chapter investigates the importance of Corporate Governance (CG) within Sri Lanka’s banking sector, recognizing its profound influence on public trust and confidence, essential for ensuring the stability of financial institutions. The chapter critically examines the state of CG development and its implications, focusing on the adequacy of regulatory frameworks provided by key legislative Acts such as the Companies Act, Banking Acts, and Securities Act and other pertinent regulations. It highlights the crucial role of a robust governance culture within the banking sector and emphasizes that banking institutions are crucial for maintaining a healthy economy. The banking industry stands as the cornerstone of Sri Lanka’s economy and operates in a highly regulated environment. Banks play a critical role by taking public deposits and facilitating financial transactions for individuals and businesses, thereby contributing significantly to economic stability and growth. Given the country’s past economic challenges, establishing solid governance practices within the banking sector is imperative for steering Sri Lanka towards a more resilient and prosperous future. The Central Bank of Sri Lanka (CBSL) emerges as a key player in this narrative, exhibiting continuous improvement in its supervisory capacity. Through the enforcement of stringent measures and the adoption of BASEL principles, the CBSL demonstrates a steadfast commitment to enhancing CG within the banking industry. Additionally, the CBSL has mandated a comprehensive code of CG, stressing the importance of full compliance from banks within a specified timeframe. However, despite these advancements, challenges persist in addressing CG issues within the banking landscape. This study sheds light on the scope, impact, and effectiveness of the supervisory and regulatory oversight of the CBSL, while also highlighting ongoing challenges. By critically evaluating regulatory frameworks and supervisory roles, this chapter aims to contribute to the ongoing discourse on advancing CG in the banking sector in Sri Lanka, ultimately fostering a more stable and resilient financial ecosystem.